Monogenic diabetes syndromes: Locus‐specific databases for Alström, Wolfram, and Thiamine‐responsive megaloblastic anemia. Issue 7 (1st June 2017) - Astuti, Dewi; Sabir, Ataf; Fulton, Piers; Zatyka, Malgorzata; Williams, Denise; Hardy, Carol; Milan, Gabriella; Favaretto, Francesca; Yu‐Wai‐Man, Patrick; Rohayem, Julia; López de Heredia, Miguel; Hershey, Tamara; et al.
Abstract : Open access mutation database for monogenic diabetes syndromes. Abstract: We developed a variant database for diabetes syndrome genes, using the Leiden Open Variation Database platform, containing observed phenotypes matched to the genetic variations. We populated it with 628 published disease‐associated variants (December 2016) for: WFS1 ( n  = 309), CISD2 ( n  = 3), ALMS1 ( n  = 268), and SLC19A2 ( n  = 48) for Wolfram type 1, Wolfram type 2, Alström, and Thiamine‐responsive megaloblastic anemia syndromes, respectively; and included 23 previously unpublished novel germline variants in WFS1 and 17 variants in ALMS1 . We then investigated genotype–phenotype relations for the WFS1 gene. The presence of biallelic loss‐of‐function variants predicted Wolfram syndrome defined by insulin‐dependent diabetes and optic atrophy, with a sensitivity of 79% (95% CI 75%–83%) and specificity of 92% (83%–97%). The presence of minor loss‐of‐function variants in WFS1 predicted isolated diabetes, isolated deafness, or isolated congenital cataracts without development of the full syndrome (sensitivity 100% [93%–100%]; specificity 78% [73%–82%]). The ability to provide a prognostic prediction based on genotype will lead to improvements in patient care and counseling. The development of the database as a repository for monogenic diabetes gene variants will allow prognostic predictions for other diabetes syndromes as next‐generation sequencing expands the repertoire of genotypes and phenotypes. The database is publicly available online athttps://lovd.euro-wabb.org .